Molecular Typing of Community-acquired Methicillin-Resistant Staphylococcus aureus Isolated from 2- to 6-year old Children by Staphylococcal Protein A and Agr Typing in Isfahan, Iran - Mobasherizadeh, Sina (Adv Biomed Res, 2021)
BACKGROUND: Methicillin-resistant Staphylococcus aureus (MRSA) has become a considerable public health concern in the entire world due to the rapid spread of this bacterium in human community; also the epidemiology of MRSA has changed, as the isolation of MRSA strains from healthy and non-healthy patients. Therefore, the objective of this study is to determine the genetic diversity and antibiotic resistance profile of community-acquired (CA)-MRSA nasal carriage in the Iranian samples. MATERIALS AND METHODS: A total of 25 CA-MRSA were isolated from the anterior nares of 410 healthy preschool children. All MRSA isolates were characterized by the detection of the toxic shock syndrome toxin-1 (TSST-1) and typed by γ-hemolysin genes, agr groups, and staphylococcal protein A (spa) typing. Kirby-Buyer antibiotic susceptibility testing was performed and interpreted as per the standard guidelines. RESULTS: A total of 25 (6.1%) MRSA isolates were recovered from the anterior nares of 410 preschool children. Sixteen isolates (64%) were positive for the TSST-1 gene. Three agr specificity groups were determined, as follows: eight (32%) isolates belonged to agr Group I, five (20%) isolates belonged to agr Group II, and 12 (48%) isolates belonged to agr Group III. The repeated profiles of these spa types of 25 isolates were organized into eight different lineages groups. Five of lineages contained a single strain, three of lineages contained two strains, and three of lineages consisted of more than three strains. CONCLUSIONS: The results of our study show that the rate of MRSA in our region is significantly high. Additionally, spa type t037 was the predominant type among CA S. aureus.